Excavations at the Jewry Wall Site, Leicester - Kenyon, Kathleen M. (Reports of the Research Committee of the Society of Antiquaries of London, 1948)
This is an account of the excavations at the Jewry Wall site in Leicester, Leicestershire, England, undertaken between 1936 and 1939. Included are descriptions of human remains and artefacts such as pottery, coins, buildings and metalwork, together with an account of the methodology used to unearth these.